Pengaruh Penggunaan Fan dan Debit Fluida terhadap Efisiensi Kerja Atmospheric Water Generator - Vidiyanto, Bagus Prabowo; Aryadi, Widya; Khoiron, Ahmad Mustamil; Anis, Samsudin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Brawijaya, 2019)
The purposes of this study are to investigate the effect of condenser cooling fan addition and airflow rate on the performance of Atmospheric Water Generator (AWG). In this work, humid air from the environment was supplied into AWG at 15 lpm. Then, it was condensed in the system with and without using a condenser cooling fan. The fan airflow rate also varied from 0.09 m3/s to 0.16 m3/s in order to better assess AWG performance. The results showed that the use of a condenser cooling fan can improve the Coefficient of Performance (COP) and the efficiency of the Atmospheric Water Generator. The average value of COPactual of 2.499 and the highest efficiency of 79.07% was achieved by an Atmosphere Water Generator equipped with a condenser cooling fan at an airflow rate of 0.16 m3/s.